1984
DOI: 10.1159/000194614
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Lung Stretch Receptors on the Cough Reflex in Rabbits

Abstract: The cough reflex in anaesthetized rabbits was elicited by irritation of the larynx with ammonia, inhalation of ammonia into the lungs, and mechanical stimulation of the tracheobronchial tree with a catheter. After block of lung stretch receptors with sulphur dioxide and virtual abolition of the Breuer-Hering inflation reflex, the cough response to all three stimuli was far less frequent and, when it occurred, was weaker especially with respect to the expiratory efforts. It is concluded that the Breuer-Hering r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0
1

Year Published

2003
2003
2006
2006

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(55 citation statements)
references
References 6 publications
(8 reference statements)
0
54
0
1
Order By: Relevance
“…Suppression of pump cell activity by antitussive drugs is unlikely to be responsible for our observations because in our study these drugs had no effect on eupneic respiratory phase durations or diaphragm EMG amplitude (Bolser et al, 1999). SAR afferent input does have an integral role in the production of tracheobronchial cough, and it is a permissive one (Hanacek et al, 1984;Sant'Ambrogio et al, 1984). Indeed, in a recent study, we found no evidence for a direct role of SAR afferent input on phase durations during tracheobronchial cough (Bolser and Davenport, 2000a).…”
Section: What Is the Role Of Putative Second Order Relay Neurons In Tmentioning
confidence: 53%
See 3 more Smart Citations
“…Suppression of pump cell activity by antitussive drugs is unlikely to be responsible for our observations because in our study these drugs had no effect on eupneic respiratory phase durations or diaphragm EMG amplitude (Bolser et al, 1999). SAR afferent input does have an integral role in the production of tracheobronchial cough, and it is a permissive one (Hanacek et al, 1984;Sant'Ambrogio et al, 1984). Indeed, in a recent study, we found no evidence for a direct role of SAR afferent input on phase durations during tracheobronchial cough (Bolser and Davenport, 2000a).…”
Section: What Is the Role Of Putative Second Order Relay Neurons In Tmentioning
confidence: 53%
“…Decreased excitability of this group of neurons would be expected to result in prolongation of cough phase durations. Indeed, unilateral vagotomy elicits exactly this effect on the cough reflex induced by ammonia in rabbits (Hanacek et al, 1984). This intervention decreased the frequency of coughing without altering the number of coughs per trial, indicating that cough phase durations were prolonged.…”
Section: What Is the Role Of Putative Second Order Relay Neurons In Tmentioning
confidence: 77%
See 2 more Smart Citations
“…The model is modified from Bolser and Davenport [29] and depicts: (a) augmented tracheal cough receptor [30] activity, (b) laryngeal cough receptors, (c) tracheal and laryngeal relay neurones (interneurones), (d) convergent relay neurones in the NTS and medial reticular formation that receive synaptic input from both tracheal and laryngeal interneurons, (e) a tracheobronchial gating mechanism, (f) a laryngeal gating mechanism that is functionally subdivided into elements controlling excitability of the cough/respiratory pattern generator [31] and the magnitude of expiratory motor drive, and (g) inspiratory and expiratory premotor neurons. Pulmonary slowly adapting stretch receptors facilitate laryngeal cough and have a permissive effect on tracheobronchial cough [32,33]. These elements have been omitted from the model for clarity.…”
Section: Discussionmentioning
confidence: 99%